Long-term spontaneous remission with active surveillance in IgG4-related pleuritis: A case report and literature review. (2019) - Makimoto, Go; Ohashi, Kadoaki; Taniguchi, Kohei; Soh, Junichi; Taniguchi, Akihiko; Miyahara, Nobuaki; Toyooka, Shinichi; Yoshino, Tadashi; Maeda, Yoshinobu; Kiura, Katsuyuki
Abstract: Pleural effusion is a relatively rare feature of IgG4-related disease (IgG4-RD). Here, we report a case of a 72-year-old woman who presented with pleural effusion. Although the pleural adenosine deaminase level was increased, surgical biopsy of the pleura and left inguinal lymph node indicated that the effusion was due to IgG4-RD. Active surveillance was initiated because serum IgG4 and pleural effusion naturally decreased and then completely disappeared. The patient has shown no recurrence for >4 years. This case suggests that pleural biopsy can be used to distinguish IgG4-RD from tuberculosis; moreover, some cases with pleural effusion could improve without treatment.